The church and ethnic diversity: a church polity approach for structural unification in the contemporary church (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2018)
This study will discuss the question on the church and ethnic diversity in the contemporary church, based on the experience of the Gereformeerde Kerke in South Africa (GKSA) in South Africa. An important presupposition of this study is that the GKSA was never divided in different church communities. Synods were divided on a racial or ethnical basis, but they remained one-church community where the different groups came together within one General Synod. The GKSA process did not aim at unification of separate and independent church communities; rather a unification of the structures of the church community that already existed in South Africa. The churches are in fact one church community, but struggle to integrate different synodal structures based on ethnicity.
Keywords: The Reformed Churches in South Africa (GKSA); Ethnicity; Church structure; Unification; Ethnic diversity